Performance of the T-SPOTⓇ.COVID test for detecting SARS-CoV-2-responsive T cells. (December 2021) - Kruse, Margaret; Dark, Chris; Aspden, Megan; Cochrane, Daniel; Competiello, Rick; Peltz, Maya; Torres, Luis; Wrighton-Smith, Peter; Dudek, Magdalena
HIGHLIGHTS: TSPOT.COVID is an ELISpot interferon gamma-release assay for SARS-CoV-2 TSPOT.COVID identifies a T cell response to SARS-CoV-2 spike S1 and N peptides 2–8 weeks post SARS-CoV-2 diagnosis TSPOT.COVID detected 98% of infections In comparison, immunoglobulin G (IgG) serology detected 83% of infections in the same period Cellular immune response activated sooner and lasted longer than antibodies Abstract: Objective: To evaluate the performance of the T-SPOT. COVID test for identifying SARS-CoV-2-responsive T-cells in participants with SARS-CoV-2 infection. Methods: The T-SPOT. COVID test uses ELISpot interferon-gamma release assay (IGRA) methodology to measure T cell responses to SARS-CoV-2 spike S1 and nucleocapsid peptides. T-SPOT. COVID and anti-N immunoglobulin (Ig) G serology tests were performed on blood from 186 patients with nucleic acid amplification test (NAAT)-confirmed-SARS-CoV-2 infection and 100 control group participants. Results: In the 2–8 weeks after NAAT-diagnosed SARS-CoV-2 infection, the T-SPOT. COVID test detected 98.4% (63 of 64) of infected participants, while anti-N IgG serology detected 82.8%. In the first 2 weeks after diagnosis, during adaptive immune response activation, there were less reactive T-SPOT. COVID responses (75.7%, 28 of 37 infected participants) and many less seropositive responses (32.4%). Response numbers tapered after 8 weeks; however, T-SPOT. COVID test continued to detect most participants with confirmed infection (83.6%, 56 of 67) and continued to out-perform serology (52.2%). T-SPOT. COVID response due to cross-reactive T cells was ruled out by demonstrating that, of 44 control group participants with T cells responsive to 4 human common cold coronavirus peptides, only 1 was T-SPOT. COVID reactive. Conclusion: The T-SPOT. COVID test performed well in detecting SARS-CoV-2-sensitized T-cells over many months.